Faktor-Faktor yang Berkontribusi terhadap Perilaku Politik dan Hasil Kerja Karyawan pada Perusahaan Sektor Perbankan - Tri Bodroastuti; Danie Budi Tjahyono (Jurnal Ilmiah Aset, 2010)
This study aims to identify the influence of individual factors and organizational factors to political behavior and the work outcomes of employees in the banking sector in five major cities in Java (Jakarta, Bandung, Semarang, Yogyakarta and Surabaya). The study also identifies the influence of political behavior directly to the work outcomes. This study adopts the theory of Stephen P. Robbins that summarizes the 6 indicators of individual factors, 9 indicators of organization factors, 9 indicators of political behavior, and 12 indicators of the work outcomes. Data collection was conducted by distributing questionnaires via e-mail. Respondents who had captured a number of 180, spread across five cities which are Jakarta (100 respondents), Bandung (20 respondents), Semarang (20 respondents), Yogyakarta (20 respondents), and Surabaya (20 respondents). The relationship between variables in this study were analyzed using Structural Equation Modeling (SEM). This study showed regression weight of individual factors to political behavior with regression coefficient of 0,230; organizational factors to political behavior with regression coefficient of 0,251; individual factors to the work outcomes with regression coefficient of 0,204; organizational factors to the work outcomes with regression coefficient of 0,173; political behavior to the work outcomes with regression coefficient of 0,295. From these results known to have significant positive influence variables of individual and organization factors to political behavior and work outcomes. Politicalbehavior is also evident in a direct and significant positive effect to work outcomes.